2017
DOI: 10.1038/srep46518
|View full text |Cite
|
Sign up to set email alerts
|

Renin-Angiotensin System Inhibitor is Associated with Lower Risk of Ensuing Chronic Kidney Disease after Functional Recovery from Acute Kidney Injury

Abstract: Acute kidney injury (AKI) is an independent risk factor for ensuing chronic kidney disease (CKD). Animal studies have demonstrated that renin-angiotensin system (RAS) inhibitor can reduce ensuing CKD after functional recovery from AKI. Here we study the association between ensuing CKD and use of RAS inhibitor including angiotensin converting enzyme inhibitor or angiotensin II type 1a receptor blocker starting after renal functional recovery in our prospectively collected observational AKI cohort. Adult patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 65 publications
(87 reference statements)
2
48
0
Order By: Relevance
“…Moreover, we have demonstrated that C20 suppressed renin expression under normal levels of calcium and phosphorus in vivo, which further indicated the beneficial role of C20 on renal protection. The down-regulation of renin expression markedly ameliorated the renal and cardiomyocyte injury [39,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we have demonstrated that C20 suppressed renin expression under normal levels of calcium and phosphorus in vivo, which further indicated the beneficial role of C20 on renal protection. The down-regulation of renin expression markedly ameliorated the renal and cardiomyocyte injury [39,42].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increased oxygen consumption and work burden in hypertrophic nephrons (Fig. 1, F) can give rise to activated renin signaling system and result eventually in glomerulosclerosis and tubulointerstitial fibrosis [39]. It has been shown that the degree of renal injury is positive association with the activity of renin [36].…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, Lai et al reported the median interval between the onset of AKI and the composite endpoints ‘stage 3 CKD or death’ was 685 days in an analysis of 634 critically ill patients with AKI not requiring dialysis. In our recent study, 39.7% patients with renal functional recovery from cardiac surgery‐associated AKI (CSA‐AKI) developed ensuing CKD during median follow‐up period of 2.99 years …”
Section: Epidemiology Of Aki‐ckd Continuummentioning
confidence: 99%
“…In our recent study, 39.7% patients with renal functional recovery from cardiac surgery-associated AKI (CSA-AKI) developed ensuing CKD during median follow-up period of 2.99 years. 35…”
Section: Epidemiology Of Aki-ckd Continuummentioning
confidence: 99%
See 1 more Smart Citation